Former Roberts Court Clerks’ Success Litigating Before the Supreme Court - Adam Feldman (Washington University Journal of Law & Policy, 2017)
This Article examines whether former Roberts Court clerks have a litigating advantage before their former bosses. Feldman’s findings suggest these clerks do have an advantage, but only under certain circumstances. The Article finds that former Roberts Court clerks have about an even chance of receiving votes from the Justices for or against the positions they argue. Feldman concludes it is when these former clerks argue positions ideologically aligned with their former Justices, they enhance their chance of success above this fifty percent threshold.
Keywords: Law Clerks; Supreme Court; Roberts Court; Litigation; Ideology